Progensa™™ PCA3 test for prostate cancer. (March 2011) - Durand, Xavier; Moutereau, Stephane; Xylinas, Evanguelos; de la Taille, Alexandre
The lack of accuracy from typical prostate cancer diagnostic tools led us to investigate new biomarkers. Prostate cancer gene 3 ( PCA3 or DD3 ) is a promising urinary biomarker of prostate cancer. This specific noncoding mRNA is highly overexpressed in more than 95% of primary prostate tumors. The feasibility of a PCA3 gene-based molecular assay based on the detection of prostate cancer cells in urine has been demonstrated, and a quantitative PCA3 urine test with the potential for general use in clinical settings was developed; the Progensa™™ (Gen-Probe Inc., San Diego, CA, USA) PCA3 urine test. Current data from the literature demonstrate the superiority of the PCA3 score over prostate-specific antigen, in terms of predictive value and specificity, albeit with a slightly lower sensitivity. These results are particularly encouraging for the specific population of patients who have a first negative biopsy, as a PCA3 assay could avoid unnecessary repeated biopsies. Furthermore, limited data have investigated a correlation between PCA3 scores and tumor volumes, as well as an ability to distinguish indolent from significant cancer. In the near future, combinations of multiple biomarkers integrating PCA3 will optimize the detection and characterization of prostate cancer.